2020
DOI: 10.3390/jcm9051576
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport after Anatomic and Reverse Total Shoulder Arthroplasty in Elderly Patients: A Systematic Review and Meta-Analysis

Abstract: The aim of this systematic review and meta-analysis was to evaluate the rate of return to sport in elderly patients who underwent anatomic (ATSA) and reverse (RTSA) total shoulder arthroplasty, to assess postoperative pain and functional outcomes and to give an overview of postoperative rehabilitation protocols. A systematic search in Pubmed-Medline, Cochrane Library, and Google Scholar was carried out to identify eligible randomized clinical trials, observational studies, or case series that evaluated the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
(147 reference statements)
0
4
0
Order By: Relevance
“…Only a few systematic reviews or meta-analyses have considered the return to sport after RSA [ 8 , 9 ]. From these reports, 74.9% [ 8 ] and 77% [ 9 ] of patients who performed sports preoperatively returned to sports after RSA. A similar proportion of 77% was reported for the RSA population from which our analysis groups were selected [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few systematic reviews or meta-analyses have considered the return to sport after RSA [ 8 , 9 ]. From these reports, 74.9% [ 8 ] and 77% [ 9 ] of patients who performed sports preoperatively returned to sports after RSA. A similar proportion of 77% was reported for the RSA population from which our analysis groups were selected [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…While clinical and radiological outcome parameters are well established and show good results after implantation [ 4 ], there is scant scientific evidence on the outcome of patients participating in sports after RSA. Two systematic reviews and meta-analysis have identified several scientific approaches made to investigate sports related outcomes after shoulder arthroplasty, yet there is a vast heterogeneity of the methodological approaches and the implants used (anatomical total shoulder arthroplasty, hemi shoulder arthroplasty, RSA), and only few medium-term outcomes with 5 years have been reported [ 8 , 9 ]. The frequency and type of sport activities undertaken by RSA patients show that return to sport participation rates are as high as 74.9–85.5% after surgery [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As life expectancy is increasing, active older patients expect better functional outcomes as well as good pain relief in order to return to their recreational activities after surgery [26]. A recent systematic review evaluated the rate of return to sport in older patients who underwent aTSA and rTSA [27]. The overall rate of return to sport was 82%.…”
Section: Outcomes Of Tsa In Older Patientsmentioning
confidence: 99%